Façonner les rôles sexués et discipliner le corps féminin : les discours de distribution de prix en Guadeloupe et en Martinique, 1905-1920 - Clara Palmiste (Amnis)
This study proposes to explore, on the basis of prize-giving speeches, the role of the republican school in shaping gender roles during the period following the secularisation of schools, in the 'old colonies', where school policy was closely linked to colonial policy, and both meant to educate and civilise populations deemed morally and intellectually inferior. In the context of the French colonial system in America, the aim is to understand their specificities, to examine the masculine and feminine models celebrated by the school and the social body, to question the interweaving of these gendered representations with other representations linked to race and class, and to see how they contribute to the maintenance of social order, to attempts to control the female body (the fear of the 'masculinisation' of young girls) and to the pursuit of a feminine ideal modelled on the metropolitan bourgeois model.